2012
DOI: 10.1109/jphotov.2011.2174337
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of Surface Passivation Methods for Lifetime Measurements on P-Type Silicon Wafers

Abstract: The effect of five different common surface passivation techniques on the measured bulk lifetime values of multiand monocrystalline p-type silicon wafers was investigated. Mono-[Czochralski (Cz) and floatzone (FZ)] and multicrystalline [mc and edge-defined film-fed growth (EFG)] silicon wafers were either deposited with a dielectric passivating layer of SiN x , Al 2 O 3 , or amorphous silicon (a-Si) or were passivated chemically with 0.08 M iodine-ethanol (IE) or 0.07 M quinhydrone-methanol (QM) solutions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Takato et al provided an early report on the quinhydrone‐ethanol/methanol based passivation scheme, achieving a very low S of ≈4 cm s −1 on high resistivity p‐type silicon, one of the lowest reported for this passivation scheme . Only Pollock et al have demonstrated a lower S of 1.3 cm s −1 , however this measurement was also performed on high resistivity p‐type silicon . Chhabra et al demonstrated that a moderate level of surface passivation is retained when the silicon samples are taken out of the quinhydrone‐methanol solution .…”
Section: Types Of Temporary Surface Passivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Takato et al provided an early report on the quinhydrone‐ethanol/methanol based passivation scheme, achieving a very low S of ≈4 cm s −1 on high resistivity p‐type silicon, one of the lowest reported for this passivation scheme . Only Pollock et al have demonstrated a lower S of 1.3 cm s −1 , however this measurement was also performed on high resistivity p‐type silicon . Chhabra et al demonstrated that a moderate level of surface passivation is retained when the silicon samples are taken out of the quinhydrone‐methanol solution .…”
Section: Types Of Temporary Surface Passivationmentioning
confidence: 99%
“…Benzyl‐alcohol based passivation schemes are regarded as a viable alternative method to I‐E and I‐M methods and generally offer better stability . In general, three benzyl species have been examined, hydroquinone (HQ), ­p‐benzoquinone (BQ), and quinhydrone (QHY), where the latter is the combination of HQ and BQ.…”
Section: Types Of Temporary Surface Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 with all images scaled to the same limits. The sample surfaces were passivated with quinhydrone methanol [22] for the measurement.…”
Section: A Lifetime Impact Of One-and Two-step High-temperature Gettmentioning
confidence: 99%
“…The mechanism of the Al 2 O 3 passivation degradation is still not clear yet. Some previous works report such degradation and attribute it either to the formation of BO complexes in the Al 2 O 3 samples [23] either to the presence of moisture in air [24]. However, the mechanisms occurring at the interface between Si and this interfacial oxide/ Al 2 O 3 is still not fully understood yet and complementary works have to be led to determine the rootcause and prevent this degradation.…”
Section: A Passivation Qualitymentioning
confidence: 99%